Inovasi Model Pembelajaran di Tengah Revolusi Digital - Yusup, Ade (Syntax Idea, 2025)
This study explores innovative learning models tailored for the digital age, which necessitates a shift in educational strategies. Education serves as a vital cornerstone for national development, yet Indonesia's education system grapples with a host of complex, multifaceted challenges, with many schools still relying on traditional teaching methods. As such, there is an urgent need to reevaluate and enhance learning models that promote active student engagement and elevate the quality of education. The aim of this study is to investigate innovative learning models that can effectively stimulate student interest in the digital landscape. To achieve this, a library research method is employed, drawing data from a variety of literature sources, including books, journals, and scholarly articles. This approach helps build a systematic understanding of the topics at hand. The findings of the study underscore the necessity for teachers to adopt creativity in developing innovative learning models suited for the digital era. Highlighted among the three primary models are flipped learning and blended learning, both designed to foster interactive, flexible, and technology-infused learning experiences. The implications of this research stress the importance of adapting educational frameworks to ensure that the role of teachers remains relevant amid advancing technology. Ultimately, innovative learning models not only leverage technology but also promote active participation from students in their educational journeys.